Heal : a shelter for the homeless in Tshwane : investigating a suitable living environment for the healing and rehabilitation of people in crisis - Viljoen, Marga (University of Pretoria, 2013)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2010.